Prediction of post-hepatectomy liver failure using gadoxetic acid-enhanced magnetic resonance imaging for hepatocellular carcinoma with portal vein invasion. Issue 130 (September 2020) - Tsujita, Yushi; Sofue, Keitaro; Komatsu, Shohei; Yamaguchi, Takeru; Ueshima, Eisuke; Ueno, Yoshiko; Kanda, Tomonori; Okada, Takuya; Nogami, Munenobu; Yamaguchi, Masato; Tsurusaki, Masakatsu; Hori, Masatoshi; et al.
Abstract: Purpose: Accurate prediction of post-hepatectomy liver failure (PHLF) is important in advanced hepatocellular carcinoma (HCC). We aimed to retrospectively evaluate the utility of gadoxetic acid-enhanced MRI for predicting PHLF in patients who underwent anatomic hepatectomy for HCC with portal vein invasion. Methods: Forty-one patients (32 men, 9 women) were included. Hepatobiliary-phase MR images were acquired 20 min after injection of gadoxetic acid using a 3D fat-suppressed T1-weighted spoiled gradient-echo sequence. Liver-spleen ratio (LSR), remnant hepatocellular uptake index (rHUI), and HUI were calculated. The severity of PHLF was defined according to the International Study Group of Liver Surgery. Differences in LSR between the resected liver and the remnant liver, and HUI and rHUI/HUI between no/mild and severe PHLF were compared using the Wilcoxon signed-rank test and Wilcoxon rank-sum test, respectively. Univariate and multivariate logistic regression analyses were performed to identify predictors of severe PHLF. Areas under the receiver operating characteristic curves (AUCs) of rHUI and rHUI/HUI were calculated for predicting severe PHLF. Results: Nine patients developed severe PHLF. LSR of the remnant liver was significantly higher than that of the resected liver ( P < 0.001). Severe PHLF demonstrated significantly lower rHUI ( P < 0.001) and rHUI/HUI ( P < 0.001) compared with no/mild PHLF. Multivariate logistic regression analysis showed that decreased rHUI ( P = 0.012, AUC=0.885) and rHUI/HUI ( P = 0.002, AUC=0.852) were independent predictors of severe PHLF. Conclusion: Gadoxetic acid-enhanced MRI can be a promising noninvasive examination for assessing global and regional liver function, allowing estimation of the functional liver remnant and accurate prediction of severe PHLF before hepatic resection.